Effectiveness of balloon pulmonary angioplasty in patients with inoperable chronic thromboembolic pulmonary hypertension despite having lesion types suitable for surgical treatment. Issue 2 (February 2020) - Minatsuki, Shun; Kiyosue, Arihiro; Kodera, Satoshi; Hara, Toru; Saito, Akihito; Maki, Hisataka; Hatano, Masaru; Takimoto, Eiki; Ando, Motomi; Komuro, Issei
Highlights: Rarely, chronic thromboembolic pulmonary hypertension with suitable lesion for pulmonary endarterectomy is judged as inoperable for any reason. Balloon pulmonary angioplasty (BPA) can improve hemodynamic status for such patients (BPA unsuitable group). Numerous BPA sessions were required compared with BPA suitable group. The occurrence of lung bleeding has no significant differences in two groups. All patients who can undergo follow-up test remained in good condition. Abstract: Background: Balloon pulmonary angioplasty (BPA) has been performed in patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH). However, some patients have inoperable CTEPH despite having lesions suitable for surgical treatment. The effectiveness of BPA in such cases is unclear. The aim of this study was to clarify the effectiveness of BPA in these cases. Methods: We retrospectively investigated patients with inoperable CTEPH and divided them into two groups: BPA-suitable and BPA-unsuitable groups based on the findings of pulmonary angiography, computed tomography, and perfusion scintigraphy. The BPA-unsuitable group included patients whose lesions are suitable for surgical treatment but who did not undergo the procedure for any specified reason. We analyzed the hemodynamic, respiratory, and functional status of the patients before and after BPA. Results: Forty-three consecutive patients with inoperable CTEPH (age, 62.6 ± 13.5 years; 31 women) were included; all of them underwent BPA. There were 10 patients in the BPA-unsuitable group. In all patients, the mean pulmonary artery pressure, pulmonary vascular resistance, arterial oxygen saturation level, and 6-min walking distance significantly improved after BPA (mean pulmonary artery pressure, from 43.3 ± 7.8 mmHg to 23.9 ± 4.7 mmHg; pulmonary vascular resistance, from 924.1 ± 462.2 dynes/s/cm −5 to 319.7 ± 163.8 dynes/s/cm −5 ; arterial oxygen saturation level, from 89.3 ± 4.3% to 93.4 ± 3.3%; 6-min walking distance, from 370.0 ± 107.4 m to 443.8 ± 101.4 m). Notably, none of the parameters significantly differed between the groups after BPA. Importantly, the amount of lung bleeding did not differ between them. However, several sessions were required in the BPA-unsuitable group (BPA-unsuitable group: six sessions vs. BPA-suitable group: four sessions). Conclusions: BPA safely improved the hemodynamic and functional statuses of the patients with CTEPH who are judged as inoperable for any reason despite lesion being suitable for surgical treatment. However, numerous BPA sessions were required in these patients.